Perlindungan Hukum Perjanjian Baku Dalam Pelayanan Jasa Asuransi di Indonesia Ditinjau Dari Perspektif Keadilan Bagi Nasabah - Ni Luh Putu Yuni Sartika Dewi; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2025)
Standard insurance agreements are used by insurance companies that do not involve customers in making policies. This agreement causes conflict in the community because the position of the parties is not balanced. Two problems are formulated: how is the legal regulation of standard agreements in the insurance service business for customers and legal protection for customers in standard agreements? The research method used is normative legal. In the insurance agreement in accordance with Insurance Law Number 40 of 2014, applying an efficient method of providing agreement documents between customers and insurance regarding the object of coverage. This causes customers to be in a weak position because they are not in a good bargaining position and only have two choices, namely accepting or rejecting it (take it or leave it). Standard agreements in insurance services are still dominant in explaining the benefits, so there are many cases of failed claims due to the information described is not comprehensive in the contents of the policy. In order for the customer's rights to be protected, all information in the policy must be explained to the customer as proof of a written agreement made by the insurance company.